Cardiovascular effects of biological versus conventional synthetic disease-modifying antirheumatic drug therapy in treatment-naïve, early rheumatoid arthritis. Issue 11 (28th August 2020) - Plein, Sven; Erhayiem, Bara; Fent, Graham; Horton, Sarah; Dumitru, Raluca Bianca; Andrews, Jacqueline; Greenwood, John P; Emery, Paul; Hensor, Elizabeth MA; Baxter, Paul; Pavitt, Sue; Buch, Maya H
Abstract : Objectives: To determine whether patients with early rheumatoid arthritis (ERA) have cardiovascular disease (CVD) that is modifiable with disease-modifying antirheumatic drug (DMARD) therapy, comparing first-line etanercept (ETN) + methotrexate (MTX) with MTX strategy. Methods: Patients from a phase IV ERA trial randomised to ETN+MTX or MTX strategy±month 6 escalation to ETN+MTX, and with no CVD and maximum one traditional risk factor underwent cardiovascular magnetic resonance (CMR) at baseline, years 1 and 2. Thirty matched controls underwent CMR. Primary outcome measure was aortic distensibility (AD) between controls and ERA, and baseline to year 1 AD change in ERA. Secondary analyses between and within ERA groups performed. Additional outcome measures included left ventricular (LV) mass and myocardial extracellular volume (ECV). Results: Eighty-one patients recruited. In ERA versus controls, respectively, baseline (geometric mean, 95% CI) AD was significantly lower (3.0×10 −3 mm Hg −1 (2.7–3.3) vs 4.4×10 −3 mm Hg −1 (3.7–5.2), p<0.001); LV mass significantly lower (78.2 g (74.0–82.7), n=81 vs 92.9 g (84.8–101.7), n=30, p<0.01); and ECV increased (27.1% (26.4–27.9), n=78 vs 24.9% (23.8–26.1), n=30, p<0.01). Across all patients, AD improved significantly from baseline to year 1 (3.0×10 −3 mm Hg −1 (2.7–3.4) to 3.6×10 –3 mm Hg −1 (3.1–4.1), respectively, p<0.01), maintained at year 2. The improvement in AD did not differ between the two treatment arms and disease activity state (Disease Activity Score with 28 joint count)-erythrocyte sedimentation rate-defined responders versus non-responders. Conclusion: We report the first evidence of vascular and myocardial abnormalities in an ERA randomised controlled trial cohort and show improvement with DMARD therapy. The type of DMARD (first-line tumour necrosis factor-inhibitors or MTX) and clinical response to therapy did not affect CVD markers. Trial registration number: ISRCTN: ISRCTN89222125 ; ClinicalTrials.gov: NCT01295151 .